Effects of epinephrine on cerebral oxygenation during cardiopulmonary resuscitation: A prospective cohort study. (December 2016) - Deakin, Charles D.; Yang, Jie; Nguyen, Robert; Zhu, Jiawen; Brett, Stephen J.; Nolan, Jerry P.; Perkins, Gavin D.; Pogson, David G.; Parnia, Sam
Abstract: Background: Epinephrine has been presumed to improve cerebral oxygen delivery during cardiopulmonary resuscitation (CPR), but animal and registry studies suggest that epinephrine-induced capillary vasoconstriction may decrease cerebral capillary blood flow and worsen neurological outcome. The effect of epinephrine on cerebral oxygenation (rSO2 ) during CPR has not been documented in the clinical setting. Methods: rSO2 was measured continuously using cerebral oximetry in patients with in-hospital cardiac arrest. During CPR, time event markers recorded the administration of 1 mg epinephrine. rSO2 values were analysed for a period beginning 5 min before and ending 5 min after the first epinephrine administration. Results: A total of 56 epinephrine doses were analysed in 36 patients during CPR. The average rSO2 value in the 5-min following epinephrine administration was 1.40% higher (95% CI = 0.41–2.40%; P = 0.0059) than in the 5-min period before epinephrine administration. However, there was no difference in the overall rate of change of rSO2 when comparing the 5-min period before, with the 5-min period immediately after a single bolus dose of epinephrine (0.88%/min vs 1.07%/min respectively; P = 0.583), There was also no difference in the changes in rSO2 at individual 1, 2, 3, or 4-min time windows before and after a bolus dose of epinephrine (P = 0.5827, 0.2371, 0.2082, and 0.6707 respectively). Conclusions: A bolus of 1 mg epinephrine IV during CPR produced a small but clinically insignificant increase in rSO2 in the five minutes after administration. This is the first clinical data to demonstrate the effects of epinephrine on cerebral rSO2 during CPR.